AKTIVITAS ANTIBAKTERI EKSTRAK METANOL KULIT BATANG TUMBUHAN SALAM (Syzygium polyanthum) TERHADAP PERTUMBUHAN BAKTERI Escherchia coli - Agni Rimba Mawan; Sri Endah Indriwati; Suhadi Suhadi (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2017)
Syzygium polyanthum has medicinal benefits, especially in its stem bark. This study aims to determine the antibacterial activity of methanol extract of Syzygium polyanthum’s stem bark to the inhibit of Escherchia coli growth. Extraction method done by maceration using methanol solvent. The extract used 40%, 60% and 80%, with tetracycline as a positive control and aquades as a negative control. Antibacterial activity tested by disk diffusion method. The result of antibacterial activity test analyzed using one-way ANOVA, followed by LSD test. The result showed that the extract concentration of 40%, 60%, and 80% have antibacterial activity with an average diameter of inhibitory zone, such as: 40% (16,2 mm),60% ( 8,5 mm) and 80% (16,3 mm), while the positive control 27,3 mm and negative control 0 mm. The results of the ANOVA analysis showed a significant value of 0.000 (p<0.05), which means there are significant differences in the effects of various concentrations of methanol extract of Syzygium polyanthum’s stem bark against Escherchia coli growth. The results of the LSD (Least Significance Different) test showed that all treatments were significantly different than concentration of 40% to consentration of 80%. The conclusion of the study is the methanol extract of Syzygium polyanthum’s stem bark have antibacterial activity against Escherchia coli. Keywords: antibacterial activity, Syzygium polyanthum, Escherchia coli, disk diffusion method